AVALIAÇÃO DA ACEITAÇÃO DAS FERRAMENTAS TECNOLÓGICAS NO AMBIENTE DO TRABALHO DOCENTE - Alberto Luís da Silva Pinto (Universidade Federal de Santa Catarina, 2019)
This research aimed to assess the worker interface with applied technologies into Distance Education environment (EaD), as well as measuring level of acceptance and effective use of the Integrated System of Management of Academic Activities (SIGAA) from the Open and Distance Education Center (CEAD) at Federal University of Piaui (UFPI). It was performed by constructs of the Technology Acceptance Model (TAM) by Davis (1989). The survey was applied to 83 tutors-professors distributed in 16 courses. It was used multivariate analysis techniques and quantitative-qualitative descriptive analysis for treatment of the data. Furthermore this paper presented a high reliability level (Alph de Cronbach de 0,83). Therefore, the tutors from the distance modality claim that are satisfied with the SIGAA, because they noted the use and easily of the System. It effectively is corroborated by Attitude and Behavioral Intent for actual use of the technology.